Interest groups and government spending in Italy, 1876 - 1913 - Nadia Fiorino; Roberto Ricciuti (Center for Economic Studies and ifo Institute (CESifo), 2009)
In the last two decades of the XIX century Italy became an industrial country. Historians maintain that this process was affected by the action of some interest groups that pursued both state protection from competition and specific public expenditure programs. Starting from the economic literature of interest groups, this paper attempts to empirically investigate the role of the interest groups in public expenditure decisions in Italy from 1876 to 1913. We argue that a proper indicator of the role of interest groups is their output. The analysis suggests that government spending was sensitive to the preferences of heavy industry rather then those of textile and cereal cultivators. We therefore highlight the role of the political process in setting economic policy at the early stages of Italian development.
Keywords: H11; N43; 330; special interest groups; public expenditure; Italian economic history; Industrialisierung; Interessenvertretung; Öffentliche Ausgaben; Wirtschaftswachstum; Italien